PERAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PEMBERDAYAAN MASYARAKAT - Istiqomah, Nur; Razak, Andi Rosdianti; Wardah, Wardah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The research aims to determine the role of information and communication technology in community empowerment at the South Sulawesi Provincial Social Service. The type of research used is qualitative, descriptive in nature. The data collection techniques used were observation, documentation and interviews. The results of the research show that the role of information and communication technology has been carried out optimally in empowering the community. In this case, the role of information technology and communication in terms of informational, organizational, social development, economic development, political participation and cultural identity can be said to be effective in conveying the information provided on the website. Although there are still some people who are sometimes still hampered by an unstable network. However, the information that has been provided is in accordance with what the community needs.